Analysis of melamine migration from melamine food contact articles - Chik, Z.; Haron, D.E.M.; Ahmad, E.D.; Taha, H.; Mustafa, A.M. (2011)
Migration of melamine has been determined for 41 types of retail melamine-ware products in Malaysia. This study was initiated by the Ministry of Health, Malaysia, in the midst of public anxiety on the possibility of melamine leaching into foods that come into contact with the melamine-ware. Thus, the objective of this study was to investigate the level of melamine migration in melamine utensils available on the market. Samples of melamine tableware, including cups and plates, forks and spoons, tumblers, bowls, etc., were collected from various retail outlets. Following the test guidelines for melamine migration set by the European Committee for Standardisation (CEN 2004) with some modifications, the samples were exposed to two types of food simulants (3 acetic acid and distilled water) at three test conditions (25 degrees C (room temperature), 70 and 100 degrees C) for 30 min. Melamine analysis was carried out using LC-MS/MS with a HILIC column and mobile phase consisting of ammonium acetate/formic acid (0.05) in water and ammonium acetate/formic acid (0.05) in acetonitrile (95 : 5, v/v). The limit of quantification (LOQ) was 5 ng/ml. Melamine migration was detected from all samples. For the articles tested with distilled water, melamine migration were median (interquartile range) 22.2 (32.6), 49.3 (50.9), 84.9 (89.9) ng/ml at room temperature (25 degrees C), 70 and 100 degrees C, respectively. In 3% acetic acid, melamine migration was 31.5 (35.7), 81.5 (76.2), 122.0 (126.7) ng/ml at room temperature (25 degrees C), 70 and 100 degrees C, respectively. This study suggests that excessive heat and acidity may directly affect melamine migration from melamine-ware products. However the results showed that melamine migration in the tested items were well below the specific migration limit (SML) of 30 mg/kg (30,000 ng/ml) set out in European Commission Directive 2002/72/EC.